Does inequality lead to conflict? - Indranil Dutta; Ajit Mishra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper presents a simple model to show how distributional concerns can engender social conflict. We have a two period model, where the cost of conflict is endogenous in the sense that parties involved have full control over how much conflict they can create. We find that anticipated future inequality plays a crucial role in determining the level of conflict in the current period. The model also provides an explanation for why similar levels of inequality may exhibit drastically different levels of conflict. Further, we argue that the link between inequality and conflict may be non-monotonic. – conflict ; wealth inequality ; Nash bargaining
Keywords: C78; D31; D74; D90; 330; Sozialer Konflikt; Einkommensverteilung; Theorie